PENGARUH AGRESIVITAS PAJAK TERHADAP CORPORATE SOCIAL RESPONSIBILITY : UNTUK MENGUJI TEORI LEGISTIMASI (Studi Empiris Pada Perusahaan Pertambangan dan Properti yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2012) - Natasya Elma Octaviana; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of corporate tax aggressiveness with corporate social resposibity (CSR): to test legitimacy theory. Sampling method used purposive sampling. A firm criteria  are mining and property companies listed on Indonesian Stock Exhange during 2009-2012. Samples were 30 companies for each year which was consist of 9 mining companies and 21 property companies. This study showed that the aggressiveness of corporate taxes significantly and negatively related to CSR. Companies that have a low level of aggressiveness resulting company would disclose CSR greater than the firm that does tax aggressiveness. This does not justify the legitimacy of the theory in the context of tax aggressiveness.